HUBUNGAN TINGKAT KEMAMPUAN DALAM MERAWAT DIRI DAN BAYINYA DAN BAYINYA TERHADAP TINGKAT KECEMASAN IBU PRIMIGRAVIDA TRIMESTER KE TIGA - Emilia Puspitasari Sugiyanto; Candra Hadi Prasetyo (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2018)
RELATIONSHIP OF THE ABILITY TO CARE OF YOURSELF AND HIS BABIES TO THIRD TRIMESTER PRIMIGRAVIDA ABSTRACTThe process of pregnancy is part of the cycle of human development. The physical, emotional, and social changes experienced by the mother during pregnancy will affect the mother's psychological well-being, the presence of the first child for primigravida mothers is a crisis in his life. The feeling of being able or unable to carry out the effect has an impact on his psychological changes, one of which is anxiety. This study is a quantitative study with a cross sectional approach. The analysis was conducted on 24 mothers in the third trimester primigravida at the health center Demak. The results showed that there was a relationship between the level of ability of primigravida mothers to care for themselves and their babies with primigravida maternal anxiety levels..